Analisis Pemahaman Mahasiswa tentang Kesehatan Mental dan Kecemasan sebagai Implementasi Hasil Pembelajaran Massive Open Online Course (MOOC) - Mutia Mawardah; Muhammad Fadhil Buja (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Mental health has become an increasingly important aspect of human well-being, as it enables individuals to think rationally, regulate their emotions effectively, and maintain positive social relationships. This community service program aimed to improve university students' understanding of mental health and anxiety disorders through the implementation of learning outcomes from a Massive Open Online Course (MOOC). A quantitative approach was employed using a Likert-scale questionnaire to assess students' level of mental health literacy and anxiety awareness. The findings revealed that the respondents demonstrated a good understanding of mental health and anxiety disorders. They were able to recognize the early signs of mental health problems, understand factors influencing mental well-being, identify appropriate self-care strategies to maintain mental health, acknowledge the importance of seeking professional assistance when needed, and access reliable sources of mental health information. These findings indicate that implementing MOOC-based learning can effectively enhance students' mental health literacy and promote greater awareness of anxiety-related issues, contributing to improved psychological well-being.